ABO AND Rh BLOOD GROUP CHARACTERISTICS OF PATIENTS AT VIETDUC HOSPITAL UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objective: To survey the ABO and Rh blood group distribution among patients at Viet Duc University Hospital in 2024.Subjects and methods: A retrospective, cross-sectional descriptive study. All Vietnamese patients whose ABO and Rh blood groups were determined at Viet Duc University Hospital in 2024. All EDTA anticoagulant blood samples were blood typed for ABO and Rh systems on an automated analyzer, and the ABO blood group discrepansies were checked in tube.Results: 71,695 Vietnamese patients had their blood type tested, ranging in age from 1 day old to 103 years old, with 63% being male and 37% female. Blood type A 20.627%, blood type B 30.299%, blood type O 43.494%, blood type AB 5.580%. The percentage of Rh(D)-positive is 99.812%, while Rh(D)-negative patients account for 0.188%.Conclusion: The blood group distribution in Vietnamese people follows the expected pattern, with O being the most common, followed by B, A, and AB. The Rh(D) negative rate of 0.188% is higher than previously reported in Vietnamese people.
Keywords: ABO blood group system, Rh system.